2022
DOI: 10.3390/ijms23116305
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Tumor Organoids Reveal Eminent Differences in Drug Sensitivities When Compared to 2-Dimensional Culture Systems

Abstract: Generation of organoids from urinary tract tumor samples was pioneered a few years ago. We generated organoids from two upper tract urothelial carcinomas and from one bladder cancer sample, and confirmed the expression of cytokeratins as urothelial antigens, vimentin as a mesenchymal marker, and fibroblast growth factor receptor 3 by immunohistochemistry. We investigated the dose response curves of two novel components, venetoclax versus S63845, in comparison to the clinical standard cisplatin in organoids in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 110 publications
0
13
0
Order By: Relevance
“…Information on the patients and stages of the disease is summarized in Table 1 . The tissue was minced by blade and scissors followed by enzymatic degradation as described recently [ 17 , 18 ]. Debris was removed by passing the extract through a cell strainer with 70 µm mesh size and cells were washed by centrifugation (150 g, 7 min, 20 °C).…”
Section: Methodsmentioning
confidence: 99%
“…Information on the patients and stages of the disease is summarized in Table 1 . The tissue was minced by blade and scissors followed by enzymatic degradation as described recently [ 17 , 18 ]. Debris was removed by passing the extract through a cell strainer with 70 µm mesh size and cells were washed by centrifugation (150 g, 7 min, 20 °C).…”
Section: Methodsmentioning
confidence: 99%
“…Wei and colleagues found significant differences in the sensitivities of BCa-cells and PDOs to cisplatin, venetoclax (a new Bcl-2 inhibitor), and S63845 (a novel MCL1 inhibitor). They conclude that PDOs more likely reflect the in vivo situation of BCa, affecting the reliability of preclinical test systems [ 81 ]. Yu et al have already gone a step further in their studies and established PDOs from luminal and basal resection specimens of a muscle-invasive BCa.…”
Section: Tumor Microspheroids/organoids In Urologymentioning
confidence: 99%
“…In the first report on BC PDOs, they often retained parental tumor heterogeneity [ 53 ]. It has been demonstrated that urinary tract PDOs maintained inter-individual sensitivity towards targeting and cytotoxic agents [ 54 ], which is not always true for 2D primary culture.…”
Section: Biomarkers For Ucmentioning
confidence: 99%